Parental Resources and Child Abuse and Neglect - Paxson, Christina; Waldfogel, Jane (American Economic Review, 1999)
A child's welfare is affected not only by the wealth of her parents, but also by the quality of care her parents provide. Physical abuse, neglect, and other forms of child maltreatment impose severe hardships on children and may adversely affect them as adults (Cathy Widom, 1989). We examine whether child maltreatment is affected by the socioeconomic circumstances of parents. Our hypothesis is that children are more likely to be maltreated if their parents have fewer resources. We use a broad conception of "resources." It encompasses not only income, but also parental time and the quality of parental time. For example, a low-income working single mother may be short on resources needed to parent not only because she earns a low income, but also because she may not have the physical or emotional reserves to care for her children properly at the end of the day. Likewise, an unemployed father may provide less than adequate parenting not only because his income has been reduced, but also because of the depression and loss of self-esteem that may accompany unemployment (Arthur Goldsniith et al., 1996). We use state-level panel data to analyze the impact that socioeconomic circumstances (in particular, parental work status and single parenthood) have on the incidence of child maltreatment. We find that socioeconomic circumstances do matter. States with higher fractions of children with absent fathers, and especially absent fathers and working mothers, have higher rates of child maltreatment. Nonworking fathers are also associated with higher rates of maltreatment.